How to Source and Use of Maju Jaya Building Store Funds - Wagiyo Aziz Abdurrachman; Arohman Arohman; Mita Ruliza (Enrichment : Journal of Management, 2021)
The need for capital is very supportive of business activities, because the owner must be wise in using the sources of funds that have been obtained. The benefits and objectives of the analysis of the sources and uses of funds to find out how to use the funds and where the funds are obtained from Research uses quantitative methods, in determining the relationship between variables in a population through calculations derived from samples Analysis of Sources and Use of Funds at Maju Jaya Building Stores, through; Analysis of Changes in Working Capital Reports, Analysis of sources and uses of funds, and Analysis of reports on sources and uses of Working Capital results obtained; Report on Changes in Working Capital has increased obtained from; income or profit; accumulated depreciation; and capital. These changes occurred in an increase in cash/bank balances, inventories, followed by a decrease in trade payables and others, as well as a decrease in bank loans, both working capital credit and investment credit, sources of funds obtained from company profits, a decrease in receivables and accumulated depreciation, then the use of these funds. which is used to increase cash/bank balances, payment of debts.